Unmet Need of Family Planning among Urban Slum Women in Chattogram (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2025)
Background: Unmet need for family planning is a contributory indicator for assessing reproductive health as well as family planning program. Despite targets are achieving more in urban than rural area, Chattogram city possesses the higher rate than others. This study is to determine the factor affecting unmet needs in urban slum of Chattogram. Materials and methods: It was a community based multi-centered descriptive cross sectional study following purposive sampling technique. Total 200 married women were interviewed as per inclusion criteria among 20 urban slums of Chattogram using a semi structure questionnaire from September 2022 to November 2022. Results: Mean age of the respondents was 30.29±7.44 years. Most of the respondents belong to nuclear family 72%. Most of the respondents (49%) had primary level of education and maximum were housewife (73.5%). More than half (56%) of the respondents had 2-5 living child. Although almost all respondents (93.5%) had knowledge about contraception but 139 (69.5%) respondents were using contraceptive methods where OCP (42.5%) was the commonest type followed by injectable contraceptive (22%). However, 3.5% were pregnant, which was intended, 6% were eager to conceive and 1.5% were sterile. Hence unmet need for family planning was 19.5%. Ignorance, non-cooperative husband, religious bar, lack of information, economic constraints, distance of health center from residence were the stated reasons did not allow them to use contraceptives. However, there was no significant association of unmet need with demographic factors like age, education, occupation, family type and number of living children. (p>0.05) Conclusion: Focusing on the narrated factors subject to unmet need odds, the problem could be mitigated by making proper action plan or strategies by stakeholders which ultimately improve the reproductive health and reach the goal of SDG.Chatt Maa Shi Hosp Med Coll J; Vol.23 (1); January 2024; Page 14-18